2020
DOI: 10.1371/journal.pone.0235716
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery to ascending aorta ratio by echocardiography: A strong predictor for presence and severity of pulmonary hypertension

Abstract: Background The pulmonary artery (PA) to ascending aorta diameter ratio (PA:A) has been evaluated in numerous studies analyzing cardiac magnetic resonance (CMR) and computed tomography (CT) data. Previously, no transthoracic echocardiography (TTE) cutoffs have been published. We sought to evaluate (1) the feasibility to image the pulmonary trunk in a prospective cohort, and (2) the ability of PA:A derived by TTE to predict pulmonary hypertension (PH). Methods We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Mean PAD measured in TTE among patients with PH (diagnosed upon invasive measure of mean pulmonary artery pressure [mPAP]), with measured in TTE mean PASP of 52 mm Hg, was 28.0 mm. This is in line with the current PAD cutoff point of 29.3 mm and corresponding PASP of 45 mm Hg [12]. The cutoff value of MDCT-measured PAD to identify PH (diagnosed with right heart catheterization) reported in previous studies ranges from 25 to 33.2 mm [13], and its corresponding correlation with mPAP ranged from r = 0.301 to r = 0.83 and it did not with larger PAD dimensions.…”
Section: Discussionsupporting
confidence: 89%
“…Mean PAD measured in TTE among patients with PH (diagnosed upon invasive measure of mean pulmonary artery pressure [mPAP]), with measured in TTE mean PASP of 52 mm Hg, was 28.0 mm. This is in line with the current PAD cutoff point of 29.3 mm and corresponding PASP of 45 mm Hg [12]. The cutoff value of MDCT-measured PAD to identify PH (diagnosed with right heart catheterization) reported in previous studies ranges from 25 to 33.2 mm [13], and its corresponding correlation with mPAP ranged from r = 0.301 to r = 0.83 and it did not with larger PAD dimensions.…”
Section: Discussionsupporting
confidence: 89%
“…Schneider et al reported that a ratio of pulmonary trunk diameter to ascending aorta diameter >1 provides additional information on pulmonary hypertension and should be taken into account in the context of routine assessment of pulmonary hypertension in echocardiography. 49 Subcostal views, such as the subcostal 4-ChV, are essential for detecting pericardial effusions. 50 Additionally, the inferior vena cava should be scanned to estimate right atrial pressure.…”
Section: Comprehensive Echocardiography In Long Covidmentioning
confidence: 99%
“…Schneider et al reported that a ratio of pulmonary trunk diameter to ascending aorta diameter >1 provides additional information on pulmonary hypertension and should be taken into account in the context of routine assessment of pulmonary hypertension in echocardiography 49 …”
Section: Comprehensive Echocardiography In Long Covidmentioning
confidence: 99%
“…10 A recent study also suggested a correlation of PA diameter and pulmonary hypertension (PH) diagnosed by transthoracic echocardiography. 11 The preoperative assessment of perioperative risk and operability of CTEPH patients planned for PEA still lacks strict objective definitions. However, certain preoperative characteristics are associated with favorable surgical outcomes: history of deep venous thrombosis (DVT) or pulmonary embolism (PE), no signs of right heart failure, no comorbidities, functional class II or III, clear disease concordant on all imaging modalities, bilateral lower lobe disease, pulmonary vascular resistance (PVR) < 1000 dyn/sec/cm À5 , and higher PA pulse pressure.…”
Section: Perspectivementioning
confidence: 99%
“… 10 A recent study also suggested a correlation of PA diameter and pulmonary hypertension (PH) diagnosed by transthoracic echocardiography. 11 …”
mentioning
confidence: 99%